Efecto de la biofertilización sobre el crecimiento en maceta de plantas de caña de azúcar (saccharum officinarum) - Serna Cook, Liliana; Arias Garcia, Camilo; Valencia Hernandez, Leidy Jhoana (Biotecnología en el Sector Agropecuario y Agroindustrial, 2011)
The use of microorganisms as fertilizer has demonstrated beneficial effects on plant growth and is an alternative to chemical fertilizers. However, each microor- ganism has different beneficial effects. This study evaluated the effect of appiying microorganism fertilizers, Azospirillum brasilense, Azotobacter chroccocum, and Trichoderma lignorum on the growth ofpotted sugarcane plants var CC 934418. Plant growth was measured in terms of stem diameter, stem and root length, and the number ofieaves and roots 15, 30, and 45 days after planting. Plant growth evidenced statistically significant differences among treatments. Microorganism fertilizers showed a positive effect on the growth of sugarcane plants, with Azospirillum brasilense and Trichoderma lignorum as the microorganisms that exercised the greatest effect on stem diameter, root systems, and plant foliation. Beneficial effects of Trichoderma lignorum on ieaf growth were observed. This is a new scientific contribution since this species has not been reported as promoting plant growth.